The Estimation of Local Government Expenditure Responses to Inter-Governmental Transfers - Irvine, Ian J.; Smith, J. Barry (The Review of Economics and Statistics, 1983)
Ian J. Irvine, J. Barry Smith, The Estimation of Local Government Expenditure Responses to Inter-Governmental Transfers, The Review of Economics and Statistics, Vol. 65, No. 3 (Aug., 1983), pp. 534-536